(untitled) (Research, Society and Development, 2021)
The aim this study was to analyze the quality of life (QoL) and its the association with sociodemographic and oral health data in non-institutionalized elderly individuals. This is a cross-sectional study with a sample of 225 elderly individuals aged 60 years or older from a city in Southern Brazil. For data collection, we used the quality of life scale (WHOQOL-OLD), the Geriatric Oral Health Assessment Index (GOHAI), as well as questions about sociodemographic and oral health conditions. QoL presented a mean of 62.73. Sociodemographic variables were tested in a linear regression model, and those that remained associated in the final adjusted model were: age (β = -0.25; 95% confidence interval, CI: -0.40; -0.14), daily independence (β = -0.32; 95% CI: -7.71; -3.57), and participation in social activities (β = -0.12; 95% CI: -4.31; -0.21). The elderly individuals’ oral characteristics were compared, and the following remained associated in the adjusted model: time of last visit to the dentist (β = -0.34; 95% CI: -9.50; -4.65) and oral self-perception (β = 0.30; 95% CI: 0.53; 1.18).The findings of this study showed that, being older, being dependent in life and non-participating in social activities, as well as no visiting the dentist last year were predictors of a worst QoL for the elderly, however, good self-perception of oral health was a predictor of better QoL.